2001
DOI: 10.1007/s001980170142
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Pamidronate as Treatment for Osteoporosis after Heart Transplantation: A Prospective Study

Abstract: Fractures due to osteoporosis are one of the major complications after heart transplantation, occurring mostly during the first 6 months after the graft, with an incidence ranging from 18% to 50% for vertebral fractures. Bone mineral density (BMD) decreases dramatically following the graft, at trabecular sites as well as cortical sites. This is explained by the relatively high doses of glucocorticoids used during the months following the graft, and by a long-term increase of bone turnover which is probably due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 17 publications
4
28
0
2
Order By: Relevance
“…In agreement with findings after solid-organ transplantation (Henderson et al, 1995;Ninkovic et al, 2000;Kreig et al, 2001), our results demonstrated a significant early decline in BMD at the femoral neck (but not the lumbar spine), which persisted for at least 2 years in recipients following autoSCT. There was also a significant early reduction in BMD at the trochanter but, by 2 years, the BMD at this site had returned to baseline values.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with findings after solid-organ transplantation (Henderson et al, 1995;Ninkovic et al, 2000;Kreig et al, 2001), our results demonstrated a significant early decline in BMD at the femoral neck (but not the lumbar spine), which persisted for at least 2 years in recipients following autoSCT. There was also a significant early reduction in BMD at the trochanter but, by 2 years, the BMD at this site had returned to baseline values.…”
Section: Discussionsupporting
confidence: 91%
“…Significant reductions in vertebral and non-vertebral fracture rates in postmenopausal women have been reported after only 1 year of treatment (Ensrud et al, 1997;Harris et al, 1999;Pols et al, 1999). Osteoporosis and increased risk of fragility fractures have been reported among long-term survivors of solidorgan transplantation (Henderson et al, 1995;Ninkovic et al, 2000;Kreig et al, 2001). Analysis of bone markers and bone histomorphometric assessment have demonstrated a state of high bone turnover following organ transplantation (Bishop et al, 1999;Vedi et al, 2002), although results of studies using antiresorptive drugs to prevent or retard bone loss have been conflicting (Kreig et al, 2001;Ninkovic et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second year after cardiac transplantation, BMD remained stable, although alendronate and calcitriol were discontinued (44). Similarly, studies demonstrated the efficacy of intravenous ibandronate, zolendronic acid and of pamidronate in the prevention of bone loss after renal, heart, lung, liver and bone marrow transplant recipients, independent of the time following transplantation (23, 40,41,45,46).…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Many of these studies have been small and most have not been randomized or controlled (7). Beneficial effects of pamidronate on indirect parameters, such as bone mineral density (BMD), have been shown in patients undergoing heart, liver, lung and kidney transplantation (8)(9)(10)(11)(12). One investigator suggested that aledronate is efficacious in preventing the natural course of bone loss associated with LT (13).…”
Section: Introductionmentioning
confidence: 99%